Holistic Approach in Inclusive Education: It’s Effectiveness in Addressing the Diversity of Elementary School Students' Characteristics - Wahyu Nurul Hidayah; Sofyan Hadi; Badrus Al Amin (Journal of Education and Social Science, 2025)
Inclusive education aims to provide equitable learning opportunities for all students, regardless of their diverse characteristics, including abilities, backgrounds, and needs. This study explores the effectiveness of a holistic approach in inclusive education, emphasizing strategies that address the multifaceted nature of elementary school students' diversity. By integrating academic, social, emotional, and cultural dimensions into teaching practices, the holistic approach seeks to foster a supportive and adaptable learning environment. The research evaluates key elements such as differentiated instruction, collaborative teaching, and student-centered methodologies, highlighting their role in enhancing inclusivity and promoting positive outcomes for learners. Findings reveal that a holistic approach significantly contributes to addressing the varied characteristics of students, improving engagement, academic achievement, and social integration. This study underscores the importance of adopting comprehensive and flexible strategies to create inclusive classrooms that cater to the unique needs of every child.